Arrhythmias in the Adult with Congenital Heart Disease - Balaji, Seshadri (SA Heart Journal, 2017)
Arrhythmias are an important problem in adults with congenital heart disease, whether previously operated upon or not. This article discusses the incidence, pathogenesis, diagnosis and management of arrhythmias in the adult congenital patient. Arrhythmias can be the cause or the effect of hemodynamic deterioration. Complex patients, such as those with transposition of the great arteries, tetralogy of Fallot and single ventricle problems are highly likely to have major arrhythmias during adult life. Early recognition and appropriate management can improve the patient’s life and can even prevent early death. Pacemaker placement should be considered for bradycardia. Tachyarrhythmia patients may need a combination of drug therapy, catheter ablation, pacemaker for antitachycardia pacing, or reoperation for residual structural issues combined with arrhythmia surgery. Sudden death is another major problem and risk stratification strategies will be discussed. Appropriate and early use of implantable defibrillators can also save lives.